Zaufanie w przestrzeni komunikacyjnej szkoły - Kwiatkowska, Henryka (Wydawnictwo Naukowe UAM, 2012)
Trust is a key concept in the social sciences. Becomes a significant category in educational practice. Especially in this kind of practice, chich is aimed at the development of students' interpersonal relationships, social solidarity, empathy. The purpose of this article is to show that this practice requires specific forms of teacher and student. The basis of this action is dialogue, mutual tolerance, joint conflict resolution, the action in the event of student resis-tance. In this activity, the teacher can not have a monopoly on the right, must be open to the right students.
Trust in the school space of communication
Keywords: trust; school; communication